Marketing Strategy Of Tour Packages Through Online In Travel Sumedang - Ila Karmila (SINTESA, 2023)
Marketing strategy is a very important part of the implementation of the company's overall strategy, especially in conditions of very tight competitors. Business competition in the tourism services sector is currently quite tight. Mulia Tour & Travel is a company engaged in the tourism industry, especially in the travel agency sector. In carrying out its business activities, it cannot be separated from the increasingly competitive market conditions which are marked by the proliferation of similar businesses in Sumedang Regency. Therefore a good and appropriate marketing strategy is needed, which is one of the ways that greatly determines the business in the tourism services sector so that business activities can continue. This research uses a descriptive type of research with a qualitative approach which aims to identify, describe and explain the actual situation related to the marketing strategy carried out by Mulia Tour & Travel. Methods of data collection using interviews, observation and documents. The data analysis used consisted of the data reduction stage, data presentation and conclusion drawing. The results showed that the Mulia Tour & Travel service company used a marketing mix strategy including product, price, place, promotion, human resources, physical evidence and the process of running its service business through online media. Suggestions from this research are better package travel packages, increase tour package bookings, increase promotion through the website, expand the collaboration networkoff line